Measurement properties of tools used to assess depression in adults with and without Autism Spectrum Conditions: a systematic review - Cassidy, S.A.; Bradley, L.; Bowen, E.; Wigham, S.; Rodgers, J. (Wiley, 2018)
Depression is the most commonly experienced mental health condition in adults with Autism Spectrum Conditions (ASC). However, it is unclear what tools are currently being used to assess depression in ASC, or whether tools need to be adapted for this group. This systematic review therefore aimed to identify tools used to assess depression in adults with and without ASC, and then evaluate these tools for their appropriateness and measurement properties. Medline, PsychINFO and Web of Knowledge were searched for studies of depression in: a) adults with ASC, without co-morbid intellectual disability; and b) adults from the general population without co-morbid conditions. Articles examining the measurement properties of these tools were then searched for using a methodological filter in PubMed, and the quality of the evidence was evaluated using the COSMIN checklist. Twelve articles were identified which utilised three tools to assess depression in adults with ASC, but only one article which assessed the measurement properties of one of these tools was identified and thus evaluated. Sixty-five articles were identified which utilised five tools to assess depression in general population adults, and 14 articles had assessed the measurement properties of these tools. Overall, two tools were found to be robust in their measurement properties in the general population – the Beck Depression Inventory (BDI-II), and the Patient Health Questionnaire (PHQ-9). Crucially only one study was identified from the COSMIN search, which showed weak evidence in support of the measurement properties of the BDI-II in an ASC sample. Implications for effective measurement of depression in ASC are discussed.